Acurácia das características definidoras do diagnóstico de enfermagem “estilo de vida sedentário” em portadores de hipertensão arterial - Guedes, Nirla Gomes (2008)
Accuracy of the defining characteristics of the nursing diagnosis ‘sedentary lifestyle’ in patients with arterial hypertension Facing the increasing global concern related to the physical inactivity, the NANDA taxonomy published in 2006 the nursing diagnosis ‘Sedentary lifestyle’ (SL). The identification of clinical indicators (defining characteristics), with good predition, will contribute to a better accuracy, improving the reliability on the diagnostic inference. Having seen the question from the view of the direct relation between the sedentary lifestyle and the pressoric levels, the study aimed to: identify the prevalence of the SL diagnosis in patients with arterial hypertension (AH), as well as the defining characteristics (DC) and the related factors (RF); verify the reproductibility of the DC and RF, to the establishment of the SL diagnosis in patients with AH; determine the sensitivity, the specificity and the preditive value of the DC in the SL diagnosis in patients with the AH. A transversal study done amongst 310 individuals accompanied in one of the ambulatory and practice centers in Fortaleza- CE. The data collection occured within the period of November, 2007 and March, 2008. The including criteria were: have the AH medical diagnosis; be registered in the program; and be aged between 18 and 69. The data were taken from a form, which had been subjected to a pre-test, through interview. Three evaluators have taken part in the study, they have also decided whether the SL diagnosis and their clinical indicators should be absent or not. The data were compiled in the Excel software and analised through the SPSS program 15.0 version. The level of significance adopted in the study was of 5%. All ethical recommendations were fulfilled. The population showed it was mostly feminine, retired, proceeded from the capital city, catholic, living with a partner, presented excess of diabetes mellitus. Half of the sample had been up to 56 years old, had attended school no more than the primary school years, had had per capita income up to R$ 253.33 and had also been presenting the arterial hypertension diagnosis for more than 10 years. The sample showed, according to the IPAQ classification, 40% showed low level of physical activity. After the evaluators judgement, the DC that was most frequent amongst the patients with AH was “one presents lack of physical condition”. The FRs with most and least prevalence were “lack of practice in order to do exercises” and “the impaired awareness about the benefits that the physical activity brings to health”, respectively. The prevalence of the SL was of 60% associated to the age, to the presence of diabetes and all the DCs and RFs, apart from the “impaired awareness about the benefits that the physical activity brings to health”. The most sensitive DC and the one with the greatest preditive negative values was “one presents lack of physical condition”, whereas “one chooses daily routine without physical exercise” and “one verbalises preference for activity with little physical activity” were more specified and with the most preditive positive values. The variables “one presents lack of physical condition”, “one verbalise preference for activity with little physical activity” and “lack of practice in order to do exercises”, as a whole, were identified as preditors with the SL identifying power of 85.2%. The study gave us a direction towards the diagnostic efficiency for the clinical indicators for the “sedentary lifestyle”. It is necessary that nurses take this diagnosis into account, in different contexts, in order to facilitate the promotion of more effective interventions and, consequently, having less complications derived from this response in people with AH.